Orchestrating Digital Economy to Foster Economic Resilience of Smart Cities: The Soft System Approach - Subkhan, Farid; Maarif, Mohammad Syamsul; Rochman, Nurul Taufiqu; Nugraha, Yudhistira (ETIKONOMI, 2025)
Research originality: This study provides new practical knowledge on the digital economy model and strategy to drive the resilient economy of smart cities.Research objective: This study aims to develop a digital economy management model for smart cities, a resilient economy framework for smart cities, and digital economy strategies for smart cities.  Research methods: This study employed a soft system methodology (SSM)-action approach by involving 30 digital economy and smart city experts from Jakarta, Bandung, Semarang, Surabaya, Banyuwangi, and Makassar.Empirical result: This study has successfully developed the digital economy model for smart cities by which digital technology, digital services, and digital finance are the keys. The resilient economy of smart cities is primarily characterized by economies of scale, economic structure, and economic stability. Moreover, the strategies should mainly focus on developing infrastructure and application, digital governance and policy, and digital society.Implication: The policy maker must consider critical policy interventions of the digital economy model and economic resilience goals, including budget priorities to the key digital economy strategies.JEL Classification: M21, O14, O18, P25, R11How to Cite:Subkhan, F., Maarif, M. S., Rochman, N. T., & Nugraha, Y. (2025). Orchestrating Digital Economy to Foster Economic Resilience of Smart Cities: The Soft System Approach. Etikonomi, 24(1), 315 – 334. https://doi.org/10.15408/etk.v24i1.39224.